Ensuring access to water in urban households - Bajpai, Peejush; Bhandari, Laveesh (2001)
This paper deals with how urban Indian households obtain water for their daily requirements. The link between economic status and access allows the analysis of issues such as water sharing, sole access, ability to pay, need for improvements, etc. The authors also put forth a strategy for levying user charges for different economic status households. The data reveal that poor access is accompanied with low levels of expectations of the populace. The paper stresses the need for a substantial consumer awareness campaign before embarking on any improvement programme. - Reproduced
Keywords: Drinking water